Screenwriting from the soul letters to an aspiring screenwriter - Krevolin, Richard W. 1964-
How often have you gone to the movies and come out of the theater thinking, "I could have written that!" Many of us believe we have what it takes to turn out a Hollywood blockbuster, if only we had the right tools to help us do it. Screenwriting from the Soul is that tool. It simplifies the process, and at the same time acknowledges that writing, especially screenwriting requires a great deal of patience, stamina, and faith.